Workshop report: strategic planning workshop on recovering Banana production in BBTD affected areas: community and farm household approaches - Lepoint, P.C.E.; Staver, Charles; Ajambo, S.; Rietveld, Anne M.; Kumar, P. Lava; Hanna, R.; Caruana, Marie-Line (2014)
Banana bunchy top disease (BBTD) caused by the Banana bunchy top virus (BBTV, genus Babuvirus, family Nanoviridae) renders plants unproductive and eventually kills affected plants. BBTD spreads into new fields along with infected planting material and through the banana aphid, Pentalonia nigronervosa, which is widespread in all banana and plantain-producing areas. BBTD was first reported from Africa in 1901, however, extensive spread into new production areas has been observed during the last two decades. The disease has very recently invaded Benin and Nigeria in West Africa in addition to limited spread within the Kivu provinces (Democratic Republic of Congo, DRC), neighbor to the largest banana-producing country in Africa - Uganda.Currently, Bunchy top has been recorded in 35 countries across Africa, Asia, Australia and the South Pacific Islands, including Hawaii (USA), but not in the Americas. In Africa, occurrence has been confirmed in 14 countries, namely Angola, Benin, Burundi, Cameroon, Central African Republic, Congo Republic, DRC, Egypt, Equatorial Guinea, Gabon, Malawi, Nigeria, Rwanda and Zambia.